Spatio-temporal variability of the salinity intrusion, mixing, and estuarine turbidity maximum in a tide-dominated tropical monsoon estuary. (1st August 2021) - Azhikodan, Gubash; Hlaing, Nay Oo; Yokoyama, Katsuhide; Kodama, Masashi
Abstract: The hydrodynamic processes of tropical estuaries in developing Asian countries are rarely reported due to their complex shape, high tidal range, long monsoon season with high river flows, and lack of infrastructure and technology. Therefore, this study investigates the seasonal and neap-spring tidal variability of salinity intrusion, mixing and formation of estuarine turbidity maximum (ETM) in a multi-branched estuarine system, Tanintharyi River estuary, Myanmar during the neap-spring tidal cycle in both dry and wet seasons of 2019. The salinity intrusion, mixing and ETM in the estuary exhibited both spatial and temporal (neap-spring tidal and seasonal) variability. The ETM zone was located at the high salinity region during the dry season whereas it was located at the low salinity region during the wet season. Hence, the ETM zones are not associated with a singular salinity, which is a different phenomenon that has been previously reported in tide-dominated estuaries. The spatial variability of salinity intrusion, mixing, and ETM in different branches at the same time during each season can be attributed to the effect of the length and shape of each branch. Finally, these hydrodynamic processes in the estuary were influenced by the strong tidal flow during the dry season whereas the river flow slightly dominated the tidal flow during the wet season. Highlights: Strong spatial, tidal and seasonal variability of salinity intrusion and mixing. The ETM zones are not associated with a singular salinity. The length and shape of each branches affect the salinity intrusion, mixing and ETM. Strong tidal flow affected the salinity intrusion, mixing and ETM in the dry season. Both tidal and river flows were dominant during the wet season.